Prevalence and risk factors of occupational neck pain in Chinese male fighter pilots: a cross-sectional study based on questionnaire and cervical sagittal alignment - Yang, Fengyuan; Wang, Zhong; Zhang, Hongxing; Xie, Bowen; Zhao, Hui; Gan, Lu; Li, Tengfei; Zhang, Jing; Chen, Zhiqiang; Li, Tianqi; Huang, Xiaogang; Chen, Yufei; et al. (Frontiers in Public Health, 2023)
Background: Neck pain (NP) is a common musculoskeletal disorder among fighter pilots and has become a rising concern due to its detrimental impact on military combat effectiveness. The occurrence of NP is influenced by a variety of factors, but less attention has been paid to the association of NP with demographic, occupational, and cervical sagittal characteristics in this group. This study aimed to investigate the prevalence and risk factors of NP in Chinese male fighter pilots using a questionnaire and cervical sagittal measurements. Methods: Demographic and flight-related data, as well as musculoskeletal pain information, were gathered from Chinese male fighter pilots via a self-report questionnaire. Cervical sagittal parameters were measured and subtypes were classified using standardized lateral cervical radiographs. Differences in various factors between the case and control groups were analyzed using t-tests or chi-square tests. Binary logistic regressions were conducted to explore potential risk factors contributing to NP. Predictors were presented as crude odds ratios (CORs) and adjusted odds ratios (AORs), along with their respective 95% confidence intervals (CIs). Results: A total of 185 male fighter pilots were included in this cross-sectional study. Among them, 96 (51.9%) reported experiencing NP within the previous 12 months. The multivariate regression analysis revealed that continuous flight training (AOR: 4.695, 95% CI: 2.226-9.901, P < 0.001), shoulder pain (AOR: 11.891, 95% CI: 4.671-30.268, P < 0.001), and low back pain (AOR: 3.452, 95% CI: 1.600-7.446, P = 0.002) were significantly associated with NP. Conclusions: The high 12-month prevalence of NP among Chinese male fighter pilots confirms the existence of this growing problem. Continuous flight training, shoulder pain, and low back pain have significant negative effects on pilots' neck health. Effective strategies are necessary to establish appropriate training schedules to reduce NP, and a more holistic perspective on musculoskeletal protection is needed. Given that spinal integrated balance and compensatory mechanisms may maintain individuals in a subclinical state, predicting the incidence of NP in fighter pilots based solely on sagittal characteristics in the cervical region may be inadequate.